Clinical and Biochemical Features in a Patient With Mitochondrial Fission Factor Gene Alteration - Nasca, Alessia; Nardecchia, Francesca; Commone, Anna; Semeraro, Michela; Legati, Andrea; Garavaglia, Barbara; Ghezzi, Daniele; Leuzzi, Vincenzo (Frontiers in Genetics, 2018)
Mitochondrial Fission Factor (MFF) is part of a protein complex that promotes mitochondria and peroxisome fission. Hitherto, only 5 patients have been reported harbouring mutations in MFF, all of them with the clinical features of a very early onset Leigh-like encephalopathy. We report on an 11-year-old boy with epileptic encephalopathy. He presented with neurological regression, epileptic myoclonic seizures, severe intellectual disability, microcephaly, tetraparesis, optic atrophy, and ophthalmoplegia. Brain MRI pattern was compatible with Leigh syndrome. NGS-based analysis of a gene panel for mitochondrial disorders revealed a homozygous c.892C>T (p. Arg298*) in the MFF gene. Fluorescence staining detected abnormal morphology of mitochondria and peroxisomes in fibroblasts from the patient; a strong reduction in MFF protein levels and the presence of truncated forms were observed. No biochemical alterations denoting peroxisomal disorders were found. As reported in other disorders affecting the dynamics of intracellular organelles, our patient showed clinical features suggesting both mitochondrial and peroxisomal impairment. Biochemical work-up in our case suggested an involvement of the energetic metabolism but without clear respiratory chain deficiency, while biomarkers of peroxisomal dysfunction were normal. We confirm that MFF mutations are associated with epileptic encephalopathy with Leigh-like MRI pattern.